Differential Impacts of Sub‐Daily Precipitation on Temperature Extremes Across China's Climatic Zones - Chengqing Chen; Shanshan Wang; Zhiyang Wang; Xiaoping Li (Geophysical Research Letters)
Abstract Precipitation events can effect temperature and modulate its response to climate change, yet the impact of sub‐daily precipitation on temperature extremes in China has been understudied. This study therefore focuses on the impact of precipitation on daily maximum temperature (Tmax) and daily minimum temperature (Tmin) across China's climatic regions from 1952 to 2019. Results show that precipitation‐induced cooling effects on Tmax through cloud effects and evaporative cooling, particularly in arid and semi‐humid regions. In arid regions, precipitation enhances Tmin through increased downward longwave radiation and changes in soil thermodynamics, while in humid regions, rainfall‐induced evaporative cooling suppresses Tmin. Notably, the Tmax warming trend during rainy weathers lacks statistical significance in humid regions, and Tmin consistently warms more during dry conditions. These findings reveal a saturation effect of precipitation on temperature and provide a framework for understanding precipitation‐temperature interactions, with implications for refining climate model and assessing global warming.